e-Health and Primary Care in Brazil: concepts, correlations and trends - Landsberg, Gustavo de Araújo Porto (2017)
Objetive: This paper aims to discuss e-Health and Primary Care concepts and correlations, considering current context of healthcare and health information technology in Brazil. Methods: Conceptual literature regarding to Primary Care and health information technology was selected and discussed. Results: Brazilian public health system has delivered cost-effective primary care over the last 20 years and recently a similar movement is being observed at private sector. Additionally, there is a expanding adoption of health information technology, which resources can be use to develop all core attributes of Primary Care. Conclusions: The e-Health utilization in Primary Care has potencial to improve health and reduce costs. A clear specific national policy, broad discussion over current regulation and a closer relationship between health professionals and information technology developers are needed to offer cost-effective e-Health aligned to Primary Care atributes.